Hay-box brooder - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In Ethiopia attempts have been made to brood chicks naturally with a portable hay-box brooder. A broody hen rearing and protecting only a few chicks ceases laying during incubation and brooding periods. Yet the success or failure of the brooding...